Effect of Ram Speed on the Integrity of AA6063 Extruded Profile through Porthole Die - V.N.S.U. Viswanat h Ammu; P.M. Padole; A. Agnihotri; Ravikumar Dumpala (Archives of Metallurgy and Materials, 2025)
In aluminium extrusion, porthole dies are extensively used for hollow profiles production. In this work, a porthole die with three portholes around the die centre was used to produce Aluminium Magnesium Silicon based AA6063 alloy profile. Press trials were conducted using horizontal type extrusion press of capacity 690 Ton under different ram speeds i.e. 2, 4.5 and 6 mm/s for producing profiles. Subsequently, the profiles produced were aged at 175°C for 6 hours and microstructures were observed. Further, samples drawn from extruded profiles were tested for tensile properties and hardness. X-ray diffraction (XRD) analysis was carried out for identification of phases. Further, the profiles produced were evaluated for weld strength integrity using wedge expansion test. Results indicated that grain refinement has occurred while extruding the samples from billet with initial grain size of 67 μm to profiles. Also, compression load in wedge expansion test was recorded for profiles produced at a ram speed of 2 mm/s with 22.74 ± 0.92 kN with decreasing trend of compression load for profiles extruded at 4.5 mm/s and 6 mm/s, which indicated that lower ram speed produces profiles with high weld strength integrity.